Measuring social influence, user perception, innovation attributes and user satisfaction in the enterprise resource planning context. (20th July 2009) - Hsu, Li-Ling; Chen, Jason C.H.; Weng, Chun-Chi
Over the recent years, the benefits of enterprise resource planning (ERP) system have appealed to small and medium enterprises (SMEs) rapidly. The samples come from 504 of the winners of outstanding SMEs award given by the Ministry of Economic Affairs in Taiwan. Valid questionnaires have 163 copies and have a return of 32%. The study examines critical factors that affect user behavioural intentions to system adoption and user satisfaction as the primary indicator for ERP success. The study results are as follows: (1) perceived usefulness has positive effect on user attitude to adopt; (2) user attitude to adopt has correlated to user behavioural intention to use positively; (3) perceived ease of use has correlated to perceived usefulness positively; (4) user attitude to adopt has correlated to user satisfaction positively; (5) user behavioural intention to use has correlated to user satisfaction positively and (6) social influence has been evaluated as correlated to critical mass positively. Most of hypotheses testing revealed supporting evidence for above relationships through structural equation modelling software (EQS) statistical analysis.